Risk assessment for the development of sleep respiratory disordens in elderly patients (Research, Society and Development, 2022)
This study aims to assess the risk of developing obstructive sleep apnea (OSA) in elderly patients assisted in primary health units. This is quantitative, cross-sectional chronology research, of a descriptive nature, with the evalution of individuals over 60 years old, in the interior of the Amazon, of both sexes, approved by the Research Ethics Committee. The sample was recruited in a non-probabilistic way, and selected with the help of the Family Health Team in the period between March and June 2022. A questionnaire created by the authors was used, which includes: Body Mass Index (BMI), a questionnaire of Berlin, and Stop Bang. Mallampati score and Oxygen Desaturation Index (ODI). A total of 38 eldery people were selected, with an average body mass index of 28.0kg/m2 (SD: 24.2-32.9), indicating that most of the sample was overweight. When dividing the elderly into normal weight and overweight, overweight and obese elderly people were three times more likely to have nocturnal respiratory events (p:0.0466). As follows, it was observed that there is a correlation between the general sample (r=0.53), that is the higher the BMI, the greater the number of respiratory events found in the elderly. Similar results were found (r=0.75) when observing the high BMI group with normal circumference.